Optimizing Cryptography Teaching Using E-Learning Approaches - Syaifuddin, Muhammad; Zulfi Azhar; Siregar, Saidi Ramadan; Ndururu, Eferoni (Bahasa Indonesia, 2024)
Cryptography plays a critical role in safeguarding data, making it an essential subject in information security education. Within this course, various algorithms are introduced, each requiring different levels of computational complexity. However, instructional practice has revealed frequent student errors in executing encryption and decryption processes, primarily due to limited understanding of cryptographic algorithms and mathematical procedures. Since accuracy is fundamental in cryptography, miscalculations can lead to incorrect message interpretation. To mitigate these issues, the learning process is supported by CrypTool, a digital aid designed to guide students through encryption and decryption tasks and minimize computational errors